Labor dynamics in Florida and Virginia shellfish aquaculture - Caela B. Gilsinan; Adriane K. Michaelis; Andrew M. Scheld (Aquaculture, 2026)

Impacts of offshore wind energy development on the commercial sea scallop fishery - Sarah Borsetti; Daphne M. Munroe; John M. Klinck; Andrew M. Scheld; Eileen E. Hofmann; Eric N. Powell; David B. Rudders (Ocean & Coastal Management, 2026)

What Is the Future of the Atlantic Surfclam ( Spisula solidissima ) Fishery Under Climate‐Induced Warming on the Mid‐Atlantic Bight Continental Shelf: A Multidecadal Assessment - Molly M. Spencer; Eric N. Powell; John M. Klinck; Daphne M. Munroe; Sarah Borsetti; Andrew M. Scheld; Eileen E. Hofmann; Enrique Curchitser (Fisheries Oceanography, 2026)
The Atlantic surfclam, Spisula solidissima supports a lucrative commercial fishery in the Mid‐Atlantic Bight (MAB) worth roughly $30 million in revenue per year. Rapid climate change is expected to modify the geographic range of the Atlantic surfclam, with consequences for the surfclam fishery. This study evaluated fishery‐based indicators projected from 2020 through 2095 based on anticipated changes in the geographic range and biomass of the Atlantic surfclam, using a Spatially Explicit, agent‐based Fisheries and Economics Simulator (SEFES). Simulations generally showed a positive trend in Atlantic surfclam biomass throughout the next three‐quarters of the 21 st century as the clam's range continues to shift offshore and northward along the continental shelf. A general decrease in fishing mortality rate is projected given the present fleet capacity, with a simultaneous increase in catch and landings per unit effort (LPUE), signaling future potential growth in the surfclam fishery. Regionally, forecasts show biomass expanding into deeper waters particularly off New Jersey, Long Island, and southern New England starting in the early 2050s, whereas populations on Georges Bank and off Delmarva gradually decline. Trends in time spent fishing, catch, and LPUE parallel those of biomass in each region. These results can inform managers and business interests that rely on this fishery, as well as other users of the continental shelf, to provide a basis for the development of anticipatory management for the socio‐ecological and economic impacts that may result from future changes in the Atlantic surfclam range and carrying capacity consequent of climate change.

Potential Future Impacts (2016–2055) of Offshore Wind Energy Development on the Atlantic Surfclam, Spisula solidissima , Fishery in the US Mid‐Atlantic Bight Continental Shelf - Autumn L. Moya; Eric N. Powell; Andrew M. Scheld; Sarah Borsetti; John M. Klinck; Eileen E. Hofmann; Molly M. Spencer; Enrique Curchitser; Daphne M. Munroe (Fisheries Oceanography, 2026)
Offshore wind energy development on the Mid‐Atlantic Bight (MAB) portion of the Northwestern Atlantic continental shelf could have adverse impacts on the future of the Atlantic surfclam, Spisula solidissima , fishery. The current and potential future areas designated for offshore wind energy development overlap with the present‐day and projected Atlantic surfclam fishing grounds and so could limit the fishery. Fishery impacts imposed by displacement of fishing outside wind farm areas and possible restrictions on vessel transit through the wind farms were simulated using a spatially explicit fishery model. The distribution of catch, hours fished, landings per unit effort (LPUE), time at sea, fishing mortality, and the number of fishing trips were projected for five time periods encompassing the period of 2016–2055. Simulations showed a significant decline in the mean of all fishery metrics (apart from LPUE) as the area of wind farm restrictions increased in scale. Impacts were consistently larger when vessel transit through and fishing within offshore wind areas were prohibited. Impacts were also larger for MAB regions off New Jersey and Delmarva than regions farther north and east. These simulations highlight the necessity of evaluating future conditions as warming temperatures shift the surfclam range relative to the immobile wind farm locations. The offshore wind industry must consider projected long‐term impacts of developmental expansion on surrounding sedentary benthic species and the commercially important fisheries that rely on them.

Climate‐Induced Warming on the Mid‐Atlantic Bight Continental Shelf: Predictions of the Future Distribution and Carrying Capacity of the Atlantic Surfclam ( Spisula solidissima ) and the Expanding Ecotone With the Ocean Quahog ( Arctica islandica ) - Molly M. Spencer; Eric N. Powell; John M. Klinck; Daphne M. Munroe; Alyssa M. LeClaire; Sarah Borsetti; Andrew M. Scheld; Eileen E. Hofmann; Enrique Curchitser (Fisheries Oceanography, 2026)
The Atlantic surfclam, Spisula solidissima , and ocean quahog, Arctica islandica , are biomass dominant bivalve species on the eastern North American continental shelf, both supporting lucrative commercial fisheries in the Mid‐Atlantic with a combined value of about $53.6 million in ex‐vessel revenue per year. The thermal tolerance of Atlantic surfclam is generally below 20 °C, whereas the boreal ocean quahog resides in colder waters maintained by the Mid‐Atlantic Bight Cold Pool. Climate‐induced warming of bottom water temperatures is thought to be linked to the observed distributional shift of the Atlantic surfclam population into waters historically dominated by ocean quahogs. As climate change is expected to continue, this study investigated the future distributions of the two species from years 2016 to 2095 using projected bottom water temperatures and a temperature‐dependent population dynamics model. Simulations show the progressive colonization of Atlantic surfclams offshore into the region earlier occupied by the Cold Pool throughout the 79‐year projection, beginning between the mid‐2040s and mid‐2050s, effectively compressing ocean quahog habitat on all sides. Ocean quahogs are shown to be vulnerable to climate‐induced warming on both the southern, inshore, and offshore portions of the continental shelf, ultimately restricting their habitat by the end of the 21st century to the remaining core of the Cold Pool off Long Island. Atlantic surfclams, however, are likely to be less vulnerable to climate‐induced warming, ultimately increasing their geographic footprint across the MAB. Model projections indicate a large‐scale reorganization event of the continental shelf benthic community structure throughout the remainder of the 21st century.

A Blueprint to Greener Shorelines: Advancing the Effectiveness, Sustainability, and Widespread Adoption of Coastal Nature-Based Solutions Through Transdisciplinary Research - Taylor M. Sloey; Sierra Hildebrandt; Rebecca L. Morris; Matthew V. Bilskie; Aaron Bland; David Bushek; Gabriella DiPetto; Daniel Elefant; Vincent Encomio; Ramin Familkhalili; Christine Hladik; Danielle Kreeger; et al. (Estuaries and Coasts, 2025)
Coastal nature-based solutions (NbS) have emerged as powerful tools to enhance sustainable development and ecological restoration goals. As a rapidly growing field spanning across social, political, ecological, economic, and engineering disciplines, it is critical that researchers working in coastal NbS regularly attempt to identify emerging focal areas for scientific inquiry. Following the 27th Biennial meeting of the Coastal and Estuarine Research Federation, we provide a transdisciplinary perspective (including biologists, engineers, oceanographers, geoscientists, economists, and facilitators of workforce training programs) of pertinent research questions that, if answered, will advance the effectiveness, sustainability, and widespread adoption of coastal NbS. These suggestions for future research highlight the necessity for diverse expertise and perspectives at every stage in planning, design, implementation, and monitoring coastal NbS.

Oyster reef recovery: Impacts of rotational management and restoration efforts on public fishing grounds - Alexandria R. Marquardt; Melissa Southworth; Andrew M. Scheld; Andrew Button; Roger Mann (Journal of Environmental Management, 2025)

What they live for: Adaptive strategies of Virginia’s small-scale commercial fishermen in a changing industry - Shelby B. White; Barbara Garrity-Blake; Andrew M. Scheld (Marine Policy, 2025)

Market development for an invasive fish species: Blue catfish in the Chesapeake Bay, US - Andrew M. Scheld; W. Reid Calhoun; Caela B. Gilsinan; Shelby B. White (Fisheries Research, 2024)

Valuing shoreline habitats for recreational fishing - Andrew M. Scheld; Donna M. Bilkovic; Sarah Stafford; Kathleen Powers; Susanna Musick; Amanda G. Guthrie (Ocean & Coastal Management, 2024)

Property owner shoreline modification decisions vary based on their perceptions of shoreline change and interests in ecological benefits - Amanda G. Guthrie; Sarah Stafford; Andrew M. Scheld; Karinna Nunez; Donna Marie Bilkovic (Frontiers in Marine Science, 2023)
Even under current sea level conditions, many communities are working to protect their coastlines against flooding and shoreline erosion. Coastal communities often protect their shorelines against excessive erosion by using armoring techniques (e.g., bulkheads, riprap). Yet hardened structures reduce many of the natural adaptive mechanisms present in coastal ecosystems and reduce the sustainability of the coastal system. In contrast, natural and nature-based features (e.g., living shorelines) can better protect coastal properties from storm damage and reduce erosion while also having the potential to adapt to new conditions. Since property owners are installing armoring structures more often than living shorelines, we sought to understand the factors motivating their shoreline modification decision. We surveyed property owners in Virginia, U.S. that applied for a shoreline modification permit. Most property owners, regardless of modification sought, perceive riprap revetment to be effective, able to withstand storm damage, and able to adapt to sea level rise. Interestingly, property owners that sought out living shorelines were not highly confident in living shorelines’ protection benefits. While most property owners perceived the ecological benefits of living shorelines, these benefits did not substantially impact the decision over what type of shoreline modification to implement. Our work highlights pathways that can improve coastal resilience given the important role that shoreline property owner decisions contribute to coastal community resiliency. Our results indicate there is a need to better engage property owners about the protection and adaptation benefits of living shorelines as their perceptions were not aligned with scientific assessments of living shorelines. Concurrently, coastal policies could be strengthened to support more natural approaches to shoreline management, as the more common armoring techniques are not resilient to sea level rise or storm damage.

Characterizing Changes in Participation and Diversification in Small-Scale Fisheries of Virginia, USA - Shelby B. White; Andrew M. Scheld (Coastal Management, 2022)

Understanding Structural Factors and Actor Attributes That Impact the Development of Cohesion within a Participatory Modeling Process - Taylor Goelz; Andrew Scheld; Troy Hartley; Inga Carboni (Coastal Management, 2020)

The Development of Attitudes Toward Scientific Models During a Participatory Modeling Process – The Impact of Participation and Social Network Structure - Taylor Goelz; Troy Hartley; Andrew Scheld; Inga Carboni (Frontiers in Marine Science, 2020)

Barriers to Eastern Oyster Aquaculture Expansion in Virginia - Jennifer Beckensteiner; David M. Kaplan; Andrew M. Scheld (Frontiers in Marine Science, 2020)